Rethinking bioenergy from an agricultural perspective: ethical issues raised by perennial energy crop and crop residue production for energy in the UK and Denmark - Shortall, Orla (2015)
The aim of this project is to explore the social and ethical dimensions of the agricultural production of perennial energy crop and crop residues for energy. Biomass – any living or recently living matter – is being promoted in industrialised countries as part of the transition from fossil fuels to an economy based on renewable energy. Various challenges face the use of bioenergy however. One particularly controversial and high profile example has been the use of food crop biofuels in transport which are seen to conflict with food production and to cause significant environmental damage. Suggested ways around these controversies is the production of perennial energy crops such as grasses and trees and crop residues such as straw, which are seen to require fewer inputs and less prime land. Some have analysed the controversies raised by biofuels in terms of controversies around industrial agriculture more broadly: biofuels are perceived to be large scale, monocultural, environmentally damaging and pushed by agri-business and energy interests. This project asks what type of agriculture system perennial energy crops and crop residues are seen as developing within, if at all. This was considered worth exploring because the type of system will have a large bearing on how they are received in future. To this end a theoretical framework of different paradigms of agriculture ranging from industrial agriculture at one end to alternative agriculture at the other was developed and applied to the data. Interviews with key stakeholders and analysis of key documents in the UK and Denmark were carried out to address the question of how perennial energy crops and crop residues are seen as overcoming previous controversies raised by food crop biofuels, in terms of their place in agricultural systems. The thesis argues that stakeholder’s visions of perennial energy crops and crop residues can be understood in terms of four models of agriculture: two industrial and two alternative. These are called “industrialism lite” that involves producing perennial energy crops on marginal land; life sciences integrated agriculture including the biorefinery strategy; multifunctional perennial energy crop production on environmentally marginal land; and ecologically integrated multipurpose biomass production through agroforestry production. There is also an argument which cuts across the paradigms and maintains that regardless of the type of agricultural system used very little or no biomass should be produced for the energy sector because of the scale of resources it requires and the scale of society’s energy use. These positions can be summarised as three different ways to overcome challenges raised by food crop biofuels: further industrialise agriculture; de-industrialise agriculture; and de-industrialise agriculture and reduce society’s energy use, though biomass could still only be used to a very limited extent, if at all, in energy production.